Pengelolaan Kegiatan Ekstrakurikuler Rohani Islam (Rohis) di SMAN 2 Bandung - Syifa Arintia Putri; Rahminawati, Nan; Rachmah, Huriah (UNISBA Press, 2024)
Abstract. This research was motivated by the low religious character of students at State High School 2 Bandung. The purpose of this study was to determine the increase in religious character in students. To know the results, we need to evaluate the results of the activities. It was qualitative descriptive research. Observation, interview and documentation were the techniques of collecting data. The informants in this research were Islamic Teacher and Rohis extracurricular supervisors, head of Rohis, and mathematics teacher as a representative of other subject teachers. The techniques of analyzing data were done through steps of data reduction, data display, and drawing conclusions.. The Management of Rohis extracurricular activities, the times for carrying out Rohis activities were divided into five: 1) Islamic studies of Islamic Holiday Celebration 2) Helping with women’s activities and Friday prayers 3) SmarTren namely Ramadhan Islamic boarding school activities 4) Form a class coordinator to direct students to tadarus AlQur’an every morning before studying 5) Dhuha prayer on the first Friday at 07.00 Western Indonesian Time. Supporting factors : facilities and infrastructure, headmaster with teachers and staff, students and sponsor. Obstacle factors: licensing and funds. Abstrak. Penelitian ini dilatarbelakangi oleh rendahnya karakter religius peserta didik yang ada di SMAN 2 Bandung. Tujuan dari peneliti adalah untuk mengetahui peningkatan karakter religius pada peserta didik. Untuk mengetahui hasil tersebut adalah dengan cara evaluasi hasil kegiatan. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Informan penelitian ini terdiri dari Guru PAI yang merangkap sebagai Pembina Rohis, Ketua Rohis, dan Perwakilan Guru Mata Pelajaran Matematika. Teknik analasisis data melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil yang diperoleh, pengelolaan kegiatan ekstrakurikuler Rohani Islam (Rohis) di SMAN 2 Bandung terdapat 5 kegiatan; 1) Kajian Islami setiap PHBI (Perayaan Hari Besar Islam) 2) Membantu kegiatan keputrian dan Sholat Jum’at 3) SmarTren yaitu kegiatan pesantren Ramadhan 4) Membentuk kordinator yang bertugas mengarahkan siswa untuk tadarus Al-Qur’an setiap pagi sebelum jam pembelajaran dimulai 5) Sholat Dhuha pada Jum’at pekan pertama pukul 07.00 WIB. Faktor pendukung: sarana prasana, kepala sekolah beserta guru dan staf, respon siswa, dan sponsor. Faktor penghambat: Perizinan dan dana.